2014
DOI: 10.1038/nature13949
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of autophagy by an FXR–CREB axis

Abstract: Lysosomal degradation of cytoplasmic components by autophagy is essential for cellular survival and homeostasis under nutrient-deprived conditions1–4. Acute regulation of autophagy by nutrient-sensing kinases is well defined3, 5–7, but longer-term transcriptional regulation is relatively unknown. Here we show that the fed-state sensing nuclear receptor FXR8, 9 and the fasting transcriptional activator CREB10, 11 coordinately regulate the hepatic autophagy gene network. Pharmacological activation of FXR repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
325
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(363 citation statements)
references
References 30 publications
16
325
2
Order By: Relevance
“…Moreover, we revealed that the reduction of the ULK1 protein under starvation conditions in HBSS also takes place in cells with inhibited proteasomal degradation, suggesting the involvement of some additional Several recent publications have reported the transcriptional regulation of autophagy under starvation conditions. [1][2][3][4] However, not all of these studies have been focused on the effects downstream of mRNA transcription. Potentially, upregulation of transcription factor activities contributes to an increase in the mRNA level of respective ATG genes during starvation; however, many other factors may control autophagy at the posttranscriptional level under different starvation conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we revealed that the reduction of the ULK1 protein under starvation conditions in HBSS also takes place in cells with inhibited proteasomal degradation, suggesting the involvement of some additional Several recent publications have reported the transcriptional regulation of autophagy under starvation conditions. [1][2][3][4] However, not all of these studies have been focused on the effects downstream of mRNA transcription. Potentially, upregulation of transcription factor activities contributes to an increase in the mRNA level of respective ATG genes during starvation; however, many other factors may control autophagy at the posttranscriptional level under different starvation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Because, based on some previous reports, several ATG proteins are transcriptionally upregulated under starvation conditions, [1][2][3][4] we checked the expression of ULK1 in cells under nitrogen-deprivation conditions. In contrast to the reduction of protein level, the level of ULK1 mRNA was significantly increased, suggesting that some other mechanism of the regulation of ULK1 protein expression during starvation is downstream of transcription (Fig.…”
Section: Ulk1 Protein Levels Are Rapidly Reduced During Cell Starvationmentioning
confidence: 99%
See 1 more Smart Citation
“…A complementary mechanism to regulate lipid degradation involves the nuclear receptor farnesoid X receptor (FXR; also known as the bile acid receptor), which competes with PPARα for binding to shared sites in the promoter regions of autophagy genes; when bound to the promoters of autophagy genes FXR represses their transcription in fed cells to inhibit lipophagy 74 . FXR can also inhibit the formation of a complex between the transcriptional activator cAMP response element-binding protein (CREB), which is active under conditions of fasting, and its co-activator CRTC2 to inhibit lipophagy in the liver of fed mice 75 . Collectively, these studies highlight the complexity of integrated transcriptional networks in fine-tuning lipophagy.…”
Section: Hepatic Steatosismentioning
confidence: 99%
“…89 Also, in addition to TFEB (transcription factor EB), 90 recent studies have pointed to CREB (cAMP responsive element binding protein) and PPARA (peroxisome proliferator-activated receptor a) important for the transcriptional regulation of autophagy. 91,92 The pathogenesis of AMD is strongly associated with oxidative stress. 10,18,20,93,94 Currently, there is no established prevention or therapy for early AMD.…”
Section: Discussionmentioning
confidence: 99%